2020
DOI: 10.3390/en13123179
|View full text |Cite
|
Sign up to set email alerts
|

Cooling Performance Optimization of Direct Dry Cooling System Based on Partition Adjustment of Axial Flow Fans

Abstract: Axial flow fans play key roles in the thermo-flow performance of direct dry cooling system under windy conditions, so the energy efficiency of a power generating unit can be improved by optimizing the operation strategies of the axial flow fans. In this work, various measures based on the partition adjustment of axial flow fans with constant power consumption of a 2 × 660 MW power plant are studied by computational fluid dynamics (CFD) methods. The results show that increasing the rotational speed of the windw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…In the experiments, the outlet air temperature of radiator t a2 is measured, and the temperature difference used in the experiments is the difference between the steam temperature t s and t a2 . The polynomial formula of h ' takes the following form 26 h=normaln=1Nhnormalnunormalfn1where h n is the polynomial factor and N is set to 3.…”
Section: Numerical Models and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the experiments, the outlet air temperature of radiator t a2 is measured, and the temperature difference used in the experiments is the difference between the steam temperature t s and t a2 . The polynomial formula of h ' takes the following form 26 h=normaln=1Nhnormalnunormalfn1where h n is the polynomial factor and N is set to 3.…”
Section: Numerical Models and Methodsmentioning
confidence: 99%
“…The size of grid increases from the center to the boundary for reducing the number of grids and satisfying the calculation accuracy. With the grid numbers of 2,310,748, 3,052,216, and 3,855,109, the mass flow rates of one single fan and the ACCs are obtained at various wind speeds 26 . The largest differences between the two bigger grid numbers are both lower than 0.46%, so the number of grids in the middle is adopted.…”
Section: Physical Models and Grid Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…Li [17] simulated the flow field and temperature field of the direct air-cooling condenser, calculated the correlation between the rotational speed of each fan and the condenser pressure, and suggested adjusting the fans with a relatively higher correlation with condenser pressure is beneficial to reducing condenser pressure and improving efficiency. Huang [18,19] calculated optimal fan speed adjustment strategies under different meteorological conditions and proposed adjusting the fan speed in different blocks under different wind directions. Through scale-down experiments, we found that fan array divisional regulation can help save about 13% of fan energy consumption [20].…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [26] associated fan performance with back pressure, and they found that the regulation of fans with high correlation coefficients can bring more benefits. In our previous research [27], it was concluded that windward fans with high rotational speed usually bring economic benefits to the power-generating unit. Moreover, the optimal rotational speeds of fan array are related to different environmental conditions, and the coal consumption may be decreased by reducing the fan speed appropriately under low temperature and wind speed [28].…”
Section: Introductionmentioning
confidence: 99%